Is experience in the public sector associated with Big Five personality aspects? - León, Federico R. (2017)
The hypothesis that employees with experience in the public sector differ in personality aspects from those with less or no experience, suggested by the concept of person-organization fit, was tested among 711 participants in executive extension courses of a Peruvian university who filled-in the Big Five Aspect Scales. Whereas significant differences in various personality aspects were observed along age and between males and females, public sector experience only predicted greater Openness. Women outperformed men in Openness and a significant gender x time in public sector interaction revealed that prediction of Openness from the public-sector experience was more pronounced among men. The findings suggest that, in the population studied, little personality differences are attributable to experience in the public sector. Studies are needed to evaluate the external validity of the findings. DOI: https://doi.org/10.24265/liberabit.2017.v23n1.07